THE ROLE OF COMPUTER GRAPHICS PROGRAMS IN THE PROCESS OF STUDENT EDUCATION AND THE ADVANTAGES OF USING THEM - Khusnidinova Nozima Ashurovna (Scholars Digest Publishing, 2023)
The second stage of the national personnel training program will be completed in New Uzbekistan. During the past period, new State educational standards were developed and approved for general secondary, specialized secondary, vocational and higher education types. These regulatory and legal documents are the basis for the creation of modern educational programs, scientific educational literature, dissertations, which are organically connected by subjects for all types of continuous education system, and serve to organize the educational process in a qualitative manner
Keywords: cybernetics, informatics, video technology, interactive methods, innovative technologies, imitation.